A catalyst for synthesizing low-carbon olefins from syngas, a preparation method and application thereof

CN122875281APending Publication Date: 2026-10-09UNIV OF SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611117091.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

综上所述,现有氧化物催化剂在合成气转化制低碳烯烃中,或面临组分不稳定、易失活及环境风险,或受限于本征活性不足,难以满足综合性能要求

Benefits of technology

[0025]本发明采用原子层沉积(Atomic Layer Deposition,以下简称ALD)技术,利用其自限制表面反应特性,在载体上实现了ZnO物种的高分散,形成了Zn1Ox单体或者是小团簇结构。该单体结构中Zn原子以三配位形式锚定于载体表面,与相邻的载体原子协同作用,显著提高了CO加氢生成含氧中间体(甲醇/二甲醚)的活性和选择性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875281A_ABST
    Figure CN122875281A_ABST
Patent Text Reader

Abstract

The application discloses a catalyst for synthesizing low-carbon olefins from synthesis gas and a preparation method and application thereof, and relates to the technical field of catalysts, and the technical scheme is as follows: the catalyst is a two-component catalyst, which is obtained by physically mixing a composite oxide and SAPO-34 molecular sieve. The composite oxide is obtained by depositing ZnO on the surface of a carrier through atomic layer deposition technology. The activity and stability of the metal oxide catalyst are improved by selecting the catalyst raw material and optimizing the synthesis technology, and the synthesis gas conversion process is synergistically optimized by combining with the improvement of the catalytic reaction process. The composite oxide-molecular sieve bifunctional catalyst obtained by the application has the advantages of high CO conversion rate and high low-carbon olefin selectivity, can inhibit the migration, agglomeration and reduction and volatilization of Zn, and can maintain the stability for more than 200 hours in the hydrogenation reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst technology, and more specifically, to a catalyst for the synthesis of low-carbon olefins from syngas, its preparation method, and its application. Background Technology

[0002] Low-carbon olefins (ethylene, propylene, butene) are important basic chemical raw materials, and traditional production routes mainly rely on petroleum cracking processes. With the increasing depletion of petroleum resources, developing non-petroleum routes for producing low-carbon olefins is of significant strategic importance. Catalytic conversion of syngas (CO / H2) to low-carbon olefins is one of the key pathways for the clean and efficient utilization of carbon-based resources such as coal, natural gas, or biomass. In particular, utilizing renewable energy to produce green hydrogen, and then combining it with industrial by-products or gasified coal gas, can not only achieve high-value utilization of waste carbon resources but also effectively reduce carbon emissions, which has significant economic and social implications.

[0003] Currently, the synthesis of low-carbon olefins from syngas mainly includes two catalytic routes: (1) the Fischer-Tropsch synthesis (FTS) route, which involves C–O dissociation, hydrogenation and CH4. x The intermediate polymerization process has a wide product distribution and is limited by the ASF (Anderson-Schulz-Flory) distribution. The selectivity of low carbon olefins in hydrocarbon products is difficult to exceed the upper limit of about 60%. (2) Oxide-Zeolite (OXZEO) bifunctional catalytic route: This route constructs a series catalyst to convert CO and H2 into oxygen-containing intermediates (such as methanol / dimethyl ether) on the oxide, and then performs C-C coupling on the molecular sieve to generate low carbon olefins. Through this process, the ASF distribution limitation can be overcome, and the selectivity of low carbon olefins in hydrocarbons can reach more than 80%.

[0004] In oxide-molecular sieve bifunctional catalysts, the oxide component is responsible for the activation of CO and its hydrogenation to form oxygen-containing intermediates, and is the key factor determining the overall catalytic activity. Currently, the oxide components reported in the literature for syngas conversion are mainly zinc-based composite oxides, represented by spinel and solid solution types, including spinel-type such as ZnCrO. x (Science.2016, 351, 1065-1068; Ind. Eng. Chem. Res. 2017, 56, 13392-13401; Angew. Chem. Int.Ed. 2018, 57, 4692-4696; Nat. Commun. 2019, 10, 129; Science 2023, 380, 727-730), ZnGaO x(ACS Catal. 2020, 10, 8303-8314; Nat. Commun. 2022, 13, 2742), and ZnAlO x (Angew. Chem. Int. Ed. 2018, 57, 12012-12016; Nat. Commun. 2018, 9, 3457; ACS Catal. 2019, 9, 1026-1032; Catal. Today 2021, 371, 85-92), and solid solutions such as ZnZrO. x (Angew. Chem. Int. Ed. 2016, 55, 4725-4728; ACS Catal. 2017, 7, 8544-8548; Chem. Sci. 2018, 9, 4708-471) and Zn x Ce 2-y Zr y O4 (ACS Catal. 2020, 10, 2046-2059), etc. However, currently developed spinel or solid solution-type ZnO-based catalysts still face serious problems such as easy migration and agglomeration of active components, phase separation, or reduction volatilization under high temperature and reducing atmosphere, leading to catalyst deactivation. Furthermore, ZnCrO, with relatively high activity... x The system presents environmental pollution problems. Researchers are also committed to developing Zn oxide-free systems (such as MnO (ACS Catal. 2017, 7, 2800-2804), MnGaO). x (Angew. Chem. Int. Ed. 2023, 62, e202217701) and CrMnGa (Ind. Eng. Chem. Res. 2021, 60, 13214-13222)) to avoid the problem of ZnO structural instability, but the activity of these catalysts is still relatively low. In summary, existing oxide catalysts in the conversion of syngas to low-carbon olefins either face the problems of component instability, easy deactivation and environmental risks, or are limited by insufficient intrinsic activity, making it difficult to meet the comprehensive performance requirements.

[0005] Therefore, developing an environmentally friendly oxide component that combines high activity, high selectivity, and excellent stability, and effectively coupling it with molecular sieves, is of great practical significance for achieving efficient conversion of syngas into low-carbon olefins. Summary of the Invention

[0006] The purpose of this invention is to provide a catalyst for the synthesis of low-carbon olefins from syngas, its preparation method, and its application. This catalyst can overcome the problems of easy migration, agglomeration, and reduction volatilization of active components under high temperature and reducing reaction atmosphere, while improving the activity and selectivity of CO hydrogenation to produce oxygen-containing intermediates, thereby obtaining a syngas-to-low-carbon olefins catalyst with high activity, high selectivity, and high stability.

[0007] The above-mentioned technical objective of the present invention is achieved through the following technical solution: a catalyst for the synthesis of low-carbon olefins from syngas, wherein the catalyst is a bifunctional catalyst comprising a composite oxide and a molecular sieve;

[0008] The composite oxide is a supported metal oxide, comprising a support and an active component ZnO supported on the surface of the support; the active component ZnO is mainly distributed on the surface of the support in the form of highly dispersed, high-density monomers or small clusters.

[0009] The molecular sieve is SAPO-34 molecular sieve with a CHA topology.

[0010] The present invention is further configured such that the content of Zn in the catalyst is 1~24 wt%.

[0011] The present invention further provides a method for preparing the above-mentioned catalyst: the preparation method includes the following steps:

[0012] S1. Impurities in the molecular sieve are removed by calcination to obtain the molecular sieve components;

[0013] S2. The required amount of ZnO precursor is deposited on the support by atomic layer deposition. After each deposition, the substrate is purged with an inert gas and then a reactant is introduced to convert the ZnO precursor into an active component, thereby obtaining a supported metal oxide component.

[0014] S3. Grind and mix the molecular sieve component and the supported metal oxide component, and granulate the product after grinding and mixing, specifically including tableting, crushing and sieving; to shape the powder mixture into particles of the target particle size, thereby obtaining the catalyst for syngas to produce low-carbon olefins.

[0015] The present invention is further configured such that the carrier is selected from one or more of t-ZrO2, m-ZrO2, α-Al2O3, r-TiO2, SiO2, and MgO.

[0016] The present invention is further configured such that the ZnO precursor is one or more of diethylzinc, bis(3-(N,N-dimethylamino)propyl)zinc, ethyl ketone imine zinc, and ethyl(bis(trimethylsilyl)amide)zinc.

[0017] The present invention is further configured such that the reactant is one or more selected from O2, O3, H2O, H2O2, NO and NO2.

[0018] The present invention is further configured such that: the molecular sieve is a SAPO-34 molecular sieve with low Si content; wherein the Si content is 0.01~0.07 in terms of the Si / (Si+Al+P) molar ratio.

[0019] The present invention is further configured such that: the reaction temperature of the atomic layer deposition method in S2 is 50-300℃, and the ZnO precursor is deposited 1-20 times;

[0020] In the mixture of molecular sieve component and supported metal oxide component in S3, the mass ratio of supported metal oxide component to molecular sieve component is 1:1-6:1.

[0021] The present invention further provides the application of the above-mentioned catalyst as a tandem catalyst in the synthesis of low-carbon olefins.

[0022] The present invention is further configured such that: the catalyst is pretreated before use, wherein the pretreatment is to reduce the active component with hydrogen at a temperature of 200~400 °C for 0.5~5 hours to partially reduce the active component;

[0023] During use: The catalyst is loaded into a fixed-bed reactor, and syngas is introduced to carry out the reaction. The main components of the syngas are CO and H2, and the volume ratio of H2 to CO is 1:1 to 3:1. The reaction conditions are: reaction temperature of 350 to 450 °C, reaction pressure of 1 to 5 MPa, and reaction space velocity of 2000 to 24000 mL·g. cat -1 ·h -1 The low-carbon olefins are C2-C4 olefins.

[0024] In summary, the present invention has the following beneficial effects:

[0025] This invention employs atomic layer deposition (ALD) technology, utilizing its self-limiting surface reaction characteristics to achieve high dispersion of ZnO species on a support, forming Zn1O. x The structure is either a monomer or a small cluster. In this monomer structure, Zn atoms are anchored to the support surface in a tricoordinate manner, and work synergistically with adjacent support atoms, significantly improving the activity and selectivity of CO hydrogenation to produce oxygen-containing intermediates (methanol / dimethyl ether).

[0026] In this invention, Zn1O xThe monomer forms a strong interfacial interaction with the support through interfacial bonding, which effectively inhibits the reduction, volatilization and migration of Zn species under reaction conditions. At the same time, it avoids the loss of ZnO active sites and the poisoning of downstream molecular sieve acidic sites by volatilized Zn species, thus endowing the catalyst with excellent long-term stability. This strong interfacial interaction also maintains the atomic-level dispersion characteristics of the active ZnO component, effectively eliminating the formation of Zn–O–Zn aggregates, thereby inhibiting the overactivation and overflow of H2 on the oxide surface, avoiding the over-hydrogenation of olefin products, and ensuring high selectivity for low-carbon olefins.

[0027] The oxide-molecular sieve bifunctional catalyst obtained by the method of this invention exhibits excellent catalytic performance in the synthesis of low-carbon olefins from syngas. It maintains a low-carbon olefin selectivity of >80% even with a CO conversion rate >55%, and the highest space-time yield of low-carbon olefins reaches 25.6 mmol·g. cat -1 ·h -1 This performance far surpasses that of existing OXZEO catalysts and Fischer-Tropsch synthesis catalysts. Furthermore, after continuous operation for over 200 hours at a high-temperature reducing atmosphere of 400 °C, no significant decrease was observed in CO conversion or low-carbon olefin selectivity, and Zn species did not aggregate or migrate to the molecular sieve. This effectively avoids the risk of deactivation of traditional ZnO-based catalysts due to the migration, aggregation, or reduction and volatilization of active components. Attached Figure Description

[0028] Figure 1 These are high-resolution transmission electron microscope (HRTEM) images of the supported oxide 1ZnO / t-ZrO2 prepared in Example 1 of this invention;

[0029] Figure 2 These are high-angle annular dark-field scanning transmission electron microscope (HAADF-STEM) and energy dispersive spectroscopy (EDS) elemental distribution characterization images of the supported oxide 1ZnO / t-ZrO2 prepared in Example 1 of this invention;

[0030] Figure 3 These are the X-ray diffraction (XRD) patterns of the supported metal oxides involved in Embodiments 1, 2, 3 and Comparative Example 1 of this invention.

[0031] Figure 4 (a) shows the X-ray absorption near-edge fine structure (XANES) spectroscopic data of the supported metal oxide 1ZnO / t-ZrO2, standard Zn foil, and ZnO prepared in Example 1 of the present invention; (b) shows the Fourier transform data of the extended edge (EXAFS) of the X-ray absorption fine structure of the supported metal oxide 1ZnO / t-ZrO2, standard Zn foil, and ZnO prepared in Example 1 of the present invention.

[0032] Figure 5 The catalytic stability of the oxide-molecular sieve bifunctional catalyst 1ZnO / t-ZrO2–SAPO-34 prepared in Example 1 of this invention;

[0033] Figure 6 (a) shows the Fourier transform data of the extended edges of the X-ray absorption fine structure of the supported metal oxides 3ZnO / t-ZrO2 and 20ZnO / t-ZrO2 prepared in Examples 2-3 of the present invention; (b) shows the Fourier transform data of the extended edges of the X-ray absorption fine structure of the supported metal oxides 1ZnO / m-ZrO2 and 1ZnO / α-Al2O3 prepared in Examples 4-5 of the present invention.

[0034] Figure 7 These are the test results of the syngas-to-low-carbon olefins performance of the oxide-molecular sieve bifunctional catalyst 1ZnO / t-ZrO2–SAPO-34 in Comparative Example 2 of this invention under different oxide / molecular sieve mass ratios.

[0035] Figure 8 The results are the performance test results of the bifunctional catalyst for syngas-to-low-carbon olefins, which integrates oxide 1ZnO / t-ZrO2 and molecular sieve SAPO-34 (0.02Si) according to the dual-bed method in Comparative Example 3 and the particle mixing method in Comparative Example 4, respectively. Detailed Implementation

[0036] The following is in conjunction with the appendix Figure 1-8 The present invention will be further described in detail below. Experimental methods not specifically described in the examples are generally performed under conventional conditions, as described in the manual, or as recommended by the manufacturer. The general equipment, materials, reagents, etc., used are commercially available unless otherwise specified. All raw materials used in the following examples and comparative examples are commercially available.

[0037] The following are explanations of relevant terms used in this invention: The term "atomic-level dispersion" refers to active metal species being loaded onto the support surface as single atoms or isolated metal-oxygen clusters, without metal-metal bonds or extended metal-oxygen-metal structures. The term "OXZEO" refers to an oxide-molecular sieve bifunctional catalytic system, in which syngas (a mixture of CO and H2) is first activated on the oxide component to form an oxygen-containing intermediate (such as methanol / dimethyl ether), which then diffuses into the molecular sieve channels for C-C coupling to generate low-carbon olefins. The term "low-carbon olefins" refers to olefins with 2 to 4 carbon atoms (i.e., C2O4 ... = -C4 =(Including ethylene, propylene, and butene). "Low-carbon olefin selectivity" refers to the mole fraction of low-carbon olefin components in all hydrocarbon products, calculated based on the number of carbon atoms, excluding CO2 byproducts. The term "space-time yield" refers to the amount of the target product generated per unit mass of catalyst per unit time, and is an important indicator for comprehensively evaluating catalyst activity, calculated based on the number of carbon atoms in the product.

[0038] In this invention, the catalyst support that can be used is a metal oxide support, examples of which can be one or more selected from t-ZrO2, m-ZrO2, α-Al2O3, r-TiO2, SiO2, and MgO. In the following embodiments, the t-ZrO2 support is preferred, mainly because the t-ZrO2 support has a suitable oxygen vacancy formation energy, and through the synergistic pairing of metal-oxygen bonds at the Zn–O–Zr dual interface, the stable anchoring of Zn atoms and O atoms can be achieved simultaneously.

[0039] In this invention, the active component of the supported metal oxide is Zn1O. x Monomers or highly dispersed ZnO clusters are deposited as follows: At a temperature of 50–300 °C, the desired amount of ZnO precursor is deposited onto the support one or more times using atomic layer deposition (ALD). Then, a reactant is introduced to convert the ZnO precursor into the active component, thereby obtaining a supported metal oxide. ZnO deposition can be performed one or more times to control the content of the ZnO active component in the entire supported metal oxide. More specifically, depositing the active component ZnO on the support surface may include the following steps:

[0040] The carrier is placed in a reactor at 50-300 °C, and the precursor vapor of the active component is introduced to be deposited or adsorbed onto the surface of the carrier by atomic deposition. Optionally and preferably, the reactor or reaction chamber is then purged with an inert gas, such as nitrogen, to remove any remaining active component precursors and other reaction products.

[0041] Then, a reactant is introduced to convert the active component precursor adsorbed on the surface of the support into the desired active component ZnO; optionally and preferably, the reactor or reaction chamber is then purged with an inert gas such as nitrogen to remove any remaining reactant and other reaction products.

[0042] Finally, as needed, the above steps can be repeated once or multiple times (i.e., depositing for one or more cycles), for example, 1-20 times, to control the content of the active component in the supported metal oxide.

[0043] In this invention, based on the total weight of the metal oxide catalyst, the content of the active component ZnO, calculated as Zn element, is 1~24 wt%. Utilizing the advantages of atomic layer deposition technology—self-limiting saturation and precise control—this invention can atomically disperse ZnO on a support to construct high-density Zn1O. x Monomer active center.

[0044] In this invention, preferably, the ZnO precursor that can be used is one or more of diethylzinc, bis(3-(N,N-dimethylamino)propyl)zinc, ethyl ketone imine zinc, and ethyl(bis(trimethylsilyl)amide)zinc, but is not limited thereto.

[0045] In this invention, preferably, the oxidant used in the oxidation treatment after the deposition of the active component is one or more selected from O2, O3, H2O, H2O2, NO and NO2, but is not limited thereto.

[0046] In this invention, preferably, the molecular sieve used in the OXZEO bifunctional catalyst is SAPO-34 molecular sieve, and the Si content of SAPO-34 is 0.01~0.07 in terms of Si / (Si+Al+P).

[0047] In this invention, preferably, the mass ratio of oxide to molecular sieve is 1:1 to 6:1, and the integration method is to uniformly grind and mix the powder, and then press and granulate the powder to shape the catalyst into particles of the target particle size.

[0048] Based on the above preparation method, the OXZEO bifunctional catalyst obtained by the present invention can realize the synthesis of low-carbon olefins from syngas and can inhibit the sintering and volatilization of active components, and can operate with high activity and high selectivity for more than 200 hours.

[0049] In this invention, preferably, the OXZEO bifunctional catalyst is pretreated before use. More preferably, the pretreatment involves reduction with hydrogen at 200-400 °C for 0.5-5 hours, for example, reduction with hydrogen at 400 °C for 2 hours.

[0050] In this invention, preferably, in the reaction of syngas to produce low-carbon olefins, the catalyst is packed in a fixed-bed reactor, and syngas is introduced to carry out the reaction. The main components of the syngas are CO and H2, with a volume ratio of H2 to CO of 1:1 to 3:1. The reaction conditions are: reaction temperature of 350 to 450 °C, reaction pressure of 1 to 5 MPa, and reaction space velocity of 2000 to 24000 mL·g. cat -1 ·h -1 .

[0051] Example 1: Preparation and performance testing of 1ZnO / t-ZrO2 catalyst

[0052] Preparation of t-ZrO2 support: Tetragonal zirconium oxide (t-ZrO2) support was prepared using the sol-gel method. 17.7 g of zirconium n-propoxide was weighed and added to 51.6 mL of n-propanol. Ammonia was added dropwise to the solution while stirring vigorously until the pH reached 10–10.5, and stirring was continued for 1 hour. The resulting gel was filtered and dried at 100 °C for 10 hours. Finally, the dried sample was calcined at 400 °C for 4 hours in air to obtain the t-ZrO2 support.

[0053] ZnO deposition: Atomic layer deposition (ALD) was used. A self-made closed-cavity ALD reactor (ACME (Beijing) Technology Co., Ltd.) was used, with diethylzinc (DEZ) and deionized water as the zinc and oxygen sources, respectively. Ultra-high purity N2 (99.999%, Nanjing Special Gases) was used as the carrier gas and purge gas at a flow rate of 300 mL / min, the vacuum degree of the reaction chamber was 2.1 Torr, and the deposition temperature was 100 ℃. During catalyst preparation, 400 mg of t-ZrO2 support was placed in the reaction chamber. (a) DEZ vapor was introduced into the reaction chamber using high-purity N2 for 200 seconds; (b) after the DEZ source was stopped, the chamber was purged with high-purity N2 for 300 seconds; (c) water vapor was introduced into the reaction chamber for 200 seconds; (d) the water was then turned off, and the chamber was purged with high-purity N2 for 300 seconds. The sample was removed from the reaction chamber to obtain a 1ZnO / t-ZrO2 catalyst precursor (Note: the number "1" before ZnO indicates one deposition, the same applies below). The 1ZnO / t-ZrO2 sample was reduced and activated in an H2 atmosphere at 400 °C for 3 h, with a heating rate of 5 °C / min and an H2 flow rate of 30 mL / min. Inductively coupled plasma atomic emission spectrometry (ICP-AES, University of Science and Technology of China, iCAP 7400) analysis of the obtained catalyst sample showed that, based on the total weight of the obtained catalyst, the loading of metallic Zn was approximately 1.5 wt%.

[0054] Characterization of catalysts:

[0055] (1) Electron microscopy characterization: HRTEM of the obtained 1ZnO / t-ZrO2 catalyst showed that 1ZnO / t-ZrO2 maintained the lattice fringes of t-ZrO2, and no ZnO particles were observed. Figure 1 ) Elemental distribution characterization was performed using atomically resolved aberration-corrected transmission electron microscopy (AEM) with HAADF-STEM and EDS. The results are as follows: Figure 2As shown in the EDS elemental distribution map, Zn elements exhibit an atomically uniform distribution on the t-ZrO2 support, with no obvious ZnO aggregation observed, confirming that ZnO species exist in an atomically dispersed state.

[0056] (2) XRD characterization: XRD characterization was performed on the t-ZrO2 support and the 1ZnO / t-ZrO2 sample. The results are as follows: Figure 3 As shown, the XRD diffraction peaks of both the t-ZrO2 support and 1ZnO / t-ZrO2 are consistent with the standard diffraction peaks of t-ZrO2. No characteristic diffraction peaks of ZnO crystals were observed, nor was any peak shift observed, thus ruling out ZnZrO2 as a possible candidate. x The possibility of solid solution formation further proves that ZnO species exist in a highly dispersed state on the carrier surface.

[0057] (3) XAFS characterization: Figure 4 XANES and EXAFS Fourier transform spectra of 1ZnO / t-ZrO2. XANES spectrum ( Figure 4 As shown in (a), the absorption edge position and shape of 1ZnO / t-ZrO2 are similar to those of the ZnO reference sample, indicating that Zn has a +2 valence. EXAFS Fourier transform spectrum ( Figure 4 As shown in (b), 1ZnO / t-ZrO2 exhibits only one main peak at 1.55 Å, belonging to the Zn–O coordination shell, both before and after hydrogen treatment. No peak belonging to the Zn–Zn shell was observed at 2.85 Å, confirming that the Zn species is atomically dispersed as Zn1O. x The presence of ZnO in monomeric form, and the same result after treatment with syngas, indicates that ZnO can still maintain atomic-level dispersion under a reactive atmosphere.

[0058] Catalyst performance evaluation:

[0059] 1ZnO / t-ZrO2 oxide and SAPO-34 molecular sieve (Si / (Si+Al+P)=0.02) were ground and mixed evenly in an agate mortar at a mass ratio of 4:1. The mixture was then pressed into tablets, crushed, and sieved at 10 MPa to obtain 40-60 mesh catalyst particles (named 1ZnO / t-ZrO2–SAPO-34). 300 mg of the catalyst was loaded into a 10 mm inner diameter stainless steel fixed-bed reactor (with a quartz liner). Before use, the catalyst was heated at 400 °C in 10% H2 / N2 (30 mL·min⁻¹). - ¹) In-situ reduction for 2 hours. Then switch to syngas (H₂ / CO = 3, containing 4% Ar as internal standard), and perform in-situ reduction at 400 °C, 4 MPa, and a space velocity of 6000 mL·g⁻¹. cat -1 ·h -1The reaction was carried out under the specified conditions. Products were analyzed by online gas chromatography, equipped with one TCD and two FID detectors. CO conversion was calculated based on carbon atoms, and hydrocarbon product selectivity was calculated based on CO2-free baseline. For ease of comparison, the catalyst composition and results of the low-carbon olefin synthesis reaction are listed in Table 1.

[0060] The evaluation results (Table 1) show that the CO conversion rate of the 1ZnO / t-ZrO2-SAPO-34 catalyst is 44.2%, and the low-carbon olefin (C2) conversion rate is [missing information]. = -C4 = The selectivity was 82.4%, with low-carbon alkanes (C2) being the most abundant. 0 -C4 0 The selectivity was 11.2% for CH4 and 3.0% for C5. + The selectivity was 3.4%, and the space-time yield of low-carbon olefins reached 14.7 mmol·g. cat -1 ·h -1 .

[0061] Stability testing: The above-mentioned 1ZnO / t-ZrO2-SAPO-34 catalyst was tested at 400 ℃, 4 MPa, H2 / CO=3, and 6000 mL·g. cat -1 ·h -1 A 200-hour stability test was conducted under the specified conditions. Results ( Figure 5 The results showed that the CO conversion rate remained stable at approximately 44%, the low-carbon olefin selectivity remained stable at approximately 82%, and there was no significant inactivation within 200 hours.

[0062] Example 2: Preparation and performance testing of 3ZnO / t-ZrO2 catalyst

[0063] ZnO deposition: The same t-ZrO2 support and ALD deposition conditions as in Example 1 were used, except that ZnO deposition was performed for 3 ALD cycles (denoted as 3ZnO / t-ZrO2). The Zn loading was determined to be approximately 3.4 wt% by ICP-AES. Figure 3 XRD characterization showed that the sample maintained the t-ZrO2 crystal phase structure, and no ZnO crystal phase diffraction peaks were observed. Figure 6 (a) EXAFS characterization shows a Zn–Zn peak at ~2.85 Å, indicating that some ZnO species have begun to form highly dispersed clusters.

[0064] Catalyst performance evaluation:

[0065] Following the method in Example 1, 3ZnO / t-ZrO2 and SAPO-34 (Si / (Si+Al+P)=0.02) were ground, mixed, tableted, and sieved at a mass ratio of 4:1 for performance evaluation. The evaluation results (Table 1) show that the CO conversion rate of the 3ZnO / t-ZrO2–SAPO-34 catalyst was 44.0%, the selectivity for low-carbon olefins decreased to 53.4%, the selectivity for low-carbon alkanes increased to 37.9%, the CH4 selectivity was 5.9%, and the C5 selectivity was... + The selectivity was 2.8%, and the space-time yield of low-carbon olefins decreased to 9.4 mmol·g. cat -1 ·h -1 .

[0066] Example 3: Preparation and performance testing of 20ZnO / t-ZrO2 catalyst

[0067] ZnO deposition: The same t-ZrO2 support and ALD deposition conditions as in Example 1 were used, except that ZnO deposition was performed for 20 ALD cycles (denoted as 20ZnO / t-ZrO2). ICP-AES determined the Zn loading to be approximately 23.7 wt%. Figure 3 XRD characterization showed that the sample mainly maintained the t-ZrO2 crystal phase structure, with only weak ZnO crystal phase diffraction peaks observed. Figure 6 (a) EXAFS characterization shows a relatively significant Zn–Zn peak at ~2.85 Å, indicating that the ZnO species has formed large clusters.

[0068] Catalyst performance evaluation:

[0069] Following the method in Example 1, 20ZnO / t-ZrO2 and SAPO-34 (Si / (Si+Al+P)=0.02) were ground, mixed, tableted, and sieved at a mass ratio of 4:1 for performance evaluation. The evaluation results (Table 1) show that the CO conversion rate of the 20ZnO / t-ZrO2–SAPO-34 catalyst decreased to 26%, the selectivity for low-carbon olefins decreased to 22.6%, the selectivity for low-carbon alkanes increased to 55.1%, the CH4 selectivity was 14.7%, and the C5 selectivity... + The selectivity was 7.8%, and the space-time yield of low-carbon olefins decreased to 2.3 mmol·g⁻¹. cat -1 ·h -1 .

[0070] Example 4: Preparation and performance testing of 1ZnO / m-ZrO2 catalyst

[0071] Preparation of m-ZrO2 support: Monoclinic zirconium oxide (m-ZrO2) support was prepared using the sol-gel method. 17.7 g of zirconium n-propoxide was weighed and added to 51.6 mL of n-propanol. Ammonia was added dropwise to the solution while stirring vigorously until the pH reached 10–10.5, and stirring was continued for 1 hour. The resulting gel was filtered and dried at 100 °C for 10 hours. Finally, the dried sample was calcined at 700 °C for 4 hours in air to obtain the m-ZrO2 support.

[0072] ZnO deposition: The same method as in Example 1 was used, except that the support was m-ZrO2 instead of t-ZrO2. ZnO deposition was performed on the m-ZrO2 support for one ALD cycle (denoted as 1ZnO / m-ZrO2). Figure 6 (b) EXAFS characterization showed a Zn–Zn peak at ~2.85 Å, indicating that some ZnO species formed highly dispersed small clusters.

[0073] Catalyst performance evaluation:

[0074] Following the method described in Example 1, 1ZnO / m-ZrO2 and SAPO-34 (Si / (Si+Al+P)=0.02) were ground, mixed, pressed, and sieved at a mass ratio of 4:1 for performance evaluation. The evaluation results (Table 1) show that the CO conversion rate of the 1ZnO / m-ZrO2–SAPO-34 catalyst was 27.9%, and the low-carbon olefin selectivity was 80.5%. Although the low-carbon olefin selectivity was high, the CO conversion rate was significantly lower than that of 1ZnO / t-ZrO2–SAPO-34, indicating that t-ZrO2 is a superior support phase.

[0075] Example 5: Preparation and performance testing of 1ZnO / α-Al2O3 catalyst

[0076] ZnO deposition: The same method as in Example 1 was used, except that the support was α-Al2O3 instead of t-ZrO2. ZnO deposition was performed on the α-Al2O3 support for one ALD cycle (denoted as 1ZnO / α-Al2O3). Figure 6 (b) EXAFS characterization showed a significant Zn–Zn peak at ~2.85 Å, indicating that ZnO species form large clusters.

[0077] Catalyst performance evaluation:

[0078] Following the method in Example 1, 1ZnO / α-Al2O3 and SAPO-34 (Si / (Si+Al+P)=0.02) were ground, mixed, tableted, and sieved at a mass ratio of 4:1 for performance evaluation. The evaluation results (Table 1) show that the CO conversion and low-carbon olefin selectivity of the 1ZnO / α-Al2O3–SAPO-34 catalyst were significantly lower than those of the 1ZnO / t-ZrO2–SAPO-34 catalyst, indicating that the unique surface structure of the t-ZrO2 support is crucial for stabilizing ZnO. x Monomers and achieving high catalytic activity are crucial.

[0079] Example 6: Performance testing of SAPO-34 molecular sieves with different Si contents (Si / (Si+Al+P)=0.01)

[0080] The same 1ZnO / t-ZrO2 oxide as in Example 1 was used, except that the molecular sieve was SAPO-34 with Si / (Si+Al+P)=0.01, denoted as 1ZnO / t-ZrO2–SAPO-34(0.01Si).

[0081] Catalyst performance evaluation:

[0082] Following the method in Example 1, the oxide and molecular sieve were ground and mixed at a mass ratio of 4:1, compressed into tablets, sieved, and then their performance was evaluated. The evaluation results (Table 1) show that the CO conversion rate was approximately 11%, and the selectivity for low-carbon olefins was approximately 83%. Although the selectivity was high, the CO conversion rate was significantly lower than that obtained using SAPO-34 with Si / (Si+Al+P)=0.02 (44.2%).

[0083] Example 7: Performance testing of SAPO-34 molecular sieves with different Si contents (Si / (Si+Al+P)=0.07)

[0084] The same 1ZnO / t-ZrO2 oxide as in Example 1 was used, except that the molecular sieve was SAPO-34 with Si / (Si+Al+P)=0.07, denoted as 1ZnO / t-ZrO2–SAPO-34(0.07Si).

[0085] Catalyst performance evaluation:

[0086] Following the method in Example 1, the oxide and molecular sieve were ground and mixed at a mass ratio of 4:1, compressed into tablets, sieved, and then their performance was evaluated. The evaluation results (Table 1) show that the CO conversion rate was approximately 29%, but the selectivity for low-carbon olefins decreased significantly to approximately 69%. This indicates that the excessively high silicon content leads to excessive acidity of the molecular sieve, promoting the occurrence of excessive hydrogenation side reactions of olefins.

[0087] Example 8: Performance testing at different H2 / CO ratios (H2 / CO=1)

[0088] The same 1ZnO / t-ZrO2–SAPO-34 catalyst (Si / (Si+Al+P)=0.02, OX / ZEO=4) was used as in Example 1, the difference being that the H2 / CO volume ratio of the reactant gas was 1:1 (45% CO, 45% H2, 10% Ar). The reaction conditions were 400 °C, 4 MPa, and 6000 mL·g. cat -1 ·h -1 The evaluation results (Table 1) show that the CO conversion rate was 43.7%, the selectivity for low-carbon olefins was approximately 82.1%, and the space-time yield of low-carbon olefins reached 25.6 mmol·g. cat -1 ·h -1 This space-time yield far exceeds that of all previously reported OXZEO catalysts and Fischer-Tropsch synthesis catalysts.

[0089] Example 9: Performance testing under different reaction pressures (Pressure = 2.5 MPa)

[0090] The same 1ZnO / t-ZrO2–SAPO-34 catalyst (Si / (Si+Al+P)=0.02, OX / ZEO=4) was used as in Example 1, except that the reactant gas pressure was 2.5 MPa and the space velocity was 2000 mL·g. cat -1 ·h -1 Reaction conditions: H2 / CO volume ratio 3:1 (24% CO, 72% H2, 4% Ar), 400 ℃, 4 MPa. Evaluation results (Table 1) show that the CO conversion rate was 55.3%, the selectivity for low-carbon olefins was approximately 81.5%, and the space-time yield of low-carbon olefins reached 5.8 mmol·g. cat -1 ·h -1 .

[0091] Comparative Example 1: ZnZrO x Preparation and performance testing of solid solution catalysts

[0092] ZnZrO x Preparation of solid solutions: ZnZrO was prepared by the sol-gel method. x Solid solution catalyst. Zn(NO3)2·6H2O, Zr(NO3)4·5H2O, and citric acid were dissolved in 100 mL of deionized water. After stirring for 30 minutes, the solution was slowly evaporated at 90 °C until a viscous gel was formed. Then, the solution was heated to 180 °C and held for 3 hours to completely evaporate any remaining moisture. Finally, the dried solid was ground into powder and calcined at 500 °C for 5 hours in air to obtain ZnZrO. xSolid solution (Zn / Zr molar ratio = 1:16). Figure 3 XRD characterization showed that the diffraction peaks shifted to a higher angle by about 0.3°, confirming the formation of a solid solution structure.

[0093] Catalyst performance evaluation:

[0094] ZnZrO was prepared according to the method in Example 1. x The ZnZrO3 was ground and mixed with SAPO-34 (Si / (Si+Al+P)=0.02) at a mass ratio of 4:1, then pressed into tablets, sieved, and its performance was evaluated. The evaluation results (Table 1) show that ZnZrO3... x The SAPO-34 catalyst exhibits a CO conversion rate of 28.0% and a low-carbon olefin selectivity of 63.4%. Compared to 1ZnO / t-ZrO2–SAPO-34, both the CO conversion rate and low-carbon olefin selectivity are significantly lower.

[0095] Comparative Example 2: Performance testing of different oxide / molecular sieve mass ratios (OX / ZEO=1)

[0096] The same 1ZnO / t-ZrO2 oxide and SAPO-34 molecular sieve (Si / (Si+Al+P)=0.02) as in Example 1 were used, the difference being that the mass ratio of oxide to molecular sieve was 1:1, 2:1, and 6:1. After grinding, mixing, tableting, and sieving according to the method of Example 1, performance was evaluated. Evaluation results ( Figure 7 The results show that when the mass ratio of oxides to molecular sieves is less than 4:1, both CO conversion and low-carbon olefin conversion decrease; when the ratio of oxides to molecular sieves is greater than 4:1, CO conversion remains almost unchanged, but low-carbon olefin selectivity decreases slightly. In summary, 4:1 is the optimal ratio.

[0097] Comparative Example 3: Different Mixing Methods – Dual-bed

[0098] The same ZnO / t-ZrO2 and SAPO-34 with a mass ratio of 4:1 as in Example 1 were ground, compressed, and sieved, and then packed in a dual-bed configuration (oxide upstream, molecular sieve downstream, separated by quartz wool) for performance evaluation. Evaluation results ( Figure 8 As shown in (a) and (b), the CO conversion rate obtained by the above catalyst assembly method is less than 10%, which is much lower than that obtained by powder grinding. This indicates that close contact between the oxide and the molecular sieve is crucial for the smooth progress of the tandem catalytic reaction.

[0099] Comparative Example 4: Different Mixing Methods – Granule Mixing

[0100] The same ZnO / t-ZrO2 and SAPO-34 in a mass ratio of 4:1 as in Example 1 were ground, compressed, and sieved to prepare 40-60 mesh particles. The particles were then mixed by shaking in a container before performance evaluation. Evaluation results ( Figure 8 As shown in (c), the CO conversion and low-carbon olefin selectivity obtained by the above catalyst assembly method are both lower than those obtained by powder grinding. This indicates that powder grinding can achieve the closest component contact at the nanoscale, thereby maximizing the bifunctional synergistic effect.

[0101] Table 1. Catalyst preparation process, composition, and low-carbon olefin synthesis reaction results

[0102]

[0103] In Table 1: the space-time yield is the total package result for low-carbon olefins (ethylene, propylene, and butene); C2 = -C4 = For olefin products with carbon chains of 2 to 4; C2 0 -C4 0 It is an alkane product with a carbon chain of 2 to 4; C5 + The products were hydrocarbons with a carbon chain of 5 or more; all data were obtained after 5 hours of reaction. The reaction conditions in Examples 1-5 and Comparative Example 1 were OX / ZEO = 4, H2 / CO = 3, 400°C, 4 MPa, and space velocity = 6,000 mL·g. cat -1 ·h -1 The reaction conditions in Examples 6-7 were: OX / ZEO = 4, H2 / CO = 3, 400 °C, 2.5 MPa, and space velocity = 6,000 mL·g. cat -1 ·h -1 In Example 8, the reaction conditions were: OX / ZEO = 4, H2 / CO = 1, 400 °C, 4 MPa, and space velocity = 6,000 mL·g. cat -1 ·h -1 In Example 9, the reaction conditions were: OX / ZEO = 4, H2 / CO = 3, 400 °C, 2.5 MPa, and space velocity = 2,000 mL·g. cat -1 ·h -1 .

[0104] Working Principle: In the OXZEO process for producing low-carbon olefins from syngas, ZnO-based composite oxides face two major challenges. Firstly, ZnO species readily aggregate and sinter under high-temperature reaction conditions, forming ZnO clusters or even nanoparticles. These aggregated ZnO species exhibit excessive hydrogenation activity, further hydrogenating the generated low-carbon olefins to alkanes, leading to a significant decrease in low-carbon olefin selectivity. Secondly, ZnO is easily reduced to metallic Zn and volatilized under reducing atmospheres, subsequently migrating to acidic sites on the molecular sieve, poisoning the active centers and causing rapid deactivation of the catalyst in both activity and selectivity. These two problems severely restrict the application of OXZEO catalysts.

[0105] Regulating the interaction between ZnO species and the support is key to improving ZnO stability. Specifically, when ZnO is anchored in an atomically dispersed form on the surface of an oxide support with suitable oxygen vacancy formation energy, the stable anchoring of Zn and O atoms can be achieved simultaneously through the synergistic pairing of two sets of interfacial metal-oxygen bonds, thereby effectively suppressing ZnO agglomeration, sintering, and reduction volatilization. Based on the above reasons, this invention utilizes the self-limiting saturated surface reaction characteristics and atomically precise control advantages of atomic layer deposition technology to construct high-density, atomically dispersed Zn1O on a support. x Monomer active center. Ultimately, a catalyst exhibiting high catalytic activity, high selectivity, and high stability was obtained in the syngas-to-low-carbon olefins reaction.

[0106] The method for preparing the high-performance, high-stability catalyst of this invention is simple to operate, highly reproducible, and widely applicable. Due to the self-limiting reaction and atomic-level precise control characteristics of atomic layer deposition (ALD), only about one atomic layer of ZnO is deposited on the support surface in each ALD cycle. By precisely controlling the number of deposition cycles, the ZnO species can be precisely controlled from atomic dispersion to clusters and then to nanoparticles. In one ALD cycle, Zn is anchored on the t-ZrO2 surface in a +2 valence state in an atomically dispersed form, forming Zn1O. x Monomer structure. This monomer forms a strong interfacial interaction with the support through Zn–O–Zr bonds, exhibiting a high oxygen vacancy formation energy. This effectively inhibits the sintering, reduction, volatilization, and migration of Zn species under reaction conditions, thus ensuring the structural stability of the catalyst and effectively improving its lifetime. Simultaneously, the isolated Zn1 oxide clusters synergistically interact with adjacent Zr sites, significantly promoting the activation of CO and H2, thereby endowing the catalyst with high activity.

[0107] More importantly, atomically dispersed Zn1O xThe monomer avoids the formation of excessive hydrogenation active centers (continuous ZnO clusters), effectively suppressing the overactivation of H2 and its spillover into the molecular sieve. This prevents the excessive hydrogenation of low-carbon olefins onto the molecular sieve to form alkanes, thus ensuring high selectivity for low-carbon olefins. Even at high CO conversion rates (>55%), it can still maintain a low-carbon olefin selectivity of >80%, breaking through the bottleneck of traditional OXZEO catalysts where "high conversion rate and high selectivity" are difficult to achieve simultaneously.

[0108] Furthermore, in this invention, the oxide and molecular sieve are tightly mixed at the nanoscale through grinding, maximizing the synergistic effect of the bifunctional reaction. After the oxygen-containing intermediate (methanol / dimethyl ether) is generated on the oxide, it rapidly diffuses into the adjacent molecular sieve channels to undergo C-C coupling to generate low-carbon olefins, effectively shifting the CO conversion reaction equilibrium to the right and promoting a significant increase in the space-time yield of low-carbon olefins.

[0109] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they are within the scope of the claims of the present invention.

Claims

1. A catalyst for the synthesis of low-carbon olefins from syngas, characterized in that: The catalyst is a bifunctional catalyst, comprising a composite oxide and a molecular sieve; The composite oxide is a supported metal oxide, comprising a support and an active component ZnO supported on the surface of the support; the active component ZnO is mainly distributed on the surface of the support in the form of highly dispersed, high-density monomers or small clusters. The molecular sieve is SAPO-34 molecular sieve with a CHA topology.

2. The catalyst for producing low-carbon olefins from syngas according to claim 1, characterized in that: The content of Zn in the catalyst is 1~24 wt%.

3. A method for preparing a catalyst for the synthesis of low-carbon olefins from syngas according to claim 1 or 2, characterized in that: The preparation method includes the following steps: S1. Impurities in the molecular sieve are removed by calcination to obtain the molecular sieve components; S2. The required amount of ZnO precursor is deposited on the support by atomic layer deposition. After each deposition, the substrate is purged with an inert gas and then a reactant is introduced to convert the ZnO precursor into an active component, thereby obtaining a supported metal oxide component. S3. Grind and mix the molecular sieve component and the supported metal oxide component, and granulate the product after grinding and mixing, specifically including tableting, crushing and sieving; to shape the powder mixture into particles of the target particle size, thereby obtaining the catalyst for syngas to produce low-carbon olefins.

4. The method for preparing a catalyst for the synthesis of low-carbon olefins from syngas according to claim 3, characterized in that: The support is selected from one or more of t-ZrO2, m-ZrO2, α-Al2O3, r-TiO2, SiO2, and MgO.

5. The method for preparing a catalyst for the synthesis of low-carbon olefins from syngas according to claim 3, characterized in that: The ZnO precursor is one or more of diethylzinc, bis(3-(N,N-dimethylamino)propyl)zinc, ethyl ketone imine zinc, and ethyl(bis(trimethylsilyl)amide)zinc.

6. The method for preparing a catalyst for the synthesis of low-carbon olefins from syngas according to claim 3, characterized in that: The reactant is selected from one or more of O2, O3, H2O, H2O2, NO, and NO2.

7. The method for preparing a catalyst for the synthesis of low-carbon olefins from syngas according to claim 3, characterized in that: The molecular sieve is a SAPO-34 molecular sieve with low Si content; wherein the Si content is 0.01~0.07 in terms of the Si / (Si+Al+P) molar ratio.

8. The method for preparing a catalyst for the synthesis of low-carbon olefins from syngas according to claim 3, characterized in that: The reaction temperature of atomic layer deposition in S2 is 50-300 ℃, and the ZnO precursor is deposited 1-20 times. In the mixture of molecular sieve component and supported metal oxide component in S3, the mass ratio of supported metal oxide component to molecular sieve component is 1:1-6:

1.

9. The application of a catalyst for the synthesis of low-carbon olefins from syngas according to claim 1 or 2, characterized in that: The catalyst is used as a tandem catalyst in the synthesis of low-carbon olefins.

10. The application of the catalyst for the synthesis of low-carbon olefins from syngas according to claim 9, characterized in that: The catalyst is pretreated before use, wherein the pretreatment is to reduce the active component with hydrogen at a temperature of 200~400 °C for 0.5~5 hours to partially reduce the active component; During use: The catalyst is loaded into a fixed-bed reactor, and syngas is introduced to carry out the reaction. The main components of the syngas are CO and H2, and the volume ratio of H2 to CO is 1:1 to 3:

1. The reaction conditions are: reaction temperature of 350 to 450 °C, reaction pressure of 1 to 5 MPa, and reaction space velocity of 2000 to 24000 mL·g. cat -1 ·h -1 The low-carbon olefins are C2-C4 olefins.